Penentuan Dosen Terbaik pada Proses Belajar Mengajar di STIKOM Tunas Bangsa Pematangsiantar dengan Metode Moora - Deviana Sitompul; S Sumarno; Bahrudi Efendi Damanik (LPPM STIKOM Tunas Bangsa, 2019)
Lecturers are one of the essential components in a system of organizing education in higher education. The main task of lecturers is as educators, lecturers carry out their duties and responsibilities to educate students to become individuals who have good abilities and potential. Given the importance of the role of lecturers, their existence in educational institutions must be able to motivate themselves and develop themselves, useful for maximizing work. In order to know the performance of the lecturers, it is necessary to evaluate the best lecturers at STIKOM Tunas Bangsa. Decision Support System (SPK) is a system that can be used by decision makers to decide on things from data and structured models. MOORA Method (Multi-Objective Optimization on the basis of Ratio Analysis) is a multi-objective system that optimizes two or more conflicting attributes simultaneously. By applying the MOORA method, the method can determine the best lecturer effectively and efficiently in STIKOM Tunas Bangsa Pematangsiantar.